KAJIAN MAKSIM: PERILAKU TINDAK TUTUR DENGAN PENDEKATAN PSIKOLOGI POSITIF - Rosida Tiurma Manurung (Jurnal Sosioteknologi, 2010)
Conversationalist and opponent in a certain context have to create the teamwork so that both parties can reach the same intention. The effort is accomplished using "Maksim" (Cooperative Principle). This research will be analyzed and explained the positive "Maksim". The writer interests to do this research because the expanding of the positive maksim in acting to say, communications in acting to say will become fluently, pleasant, and even can bring kindliness. A study of the positive "maksim" covers the "maksim" of wisdom, cheapness, acceptance, ordinary, proper, and sympathy. This explanation becomes important because the writer has noticed that the behavior of conversationalist society tends to be apathetical, uncared, undignified, disrespect, and less have empathy to others. The positive "maksim" in psychological approach is studied because the appearance of positive or negatif maksim depends on the psychological condition of the conversationalist. The existence of this research is psychologically expected that the negatif behavior of conversationalist can be improved and , turned into the positive behavior of conversationalist. It has become our duty to realize the importance of creating the positive atmosphere in all matter, including the Language behavior. Keywords: behavioral act to say, maksim, psychological approach, positive psychology